"You focus, I'm talking" : an exploratory case study of mobile phones as mediating artefacts in an advanced EFL class - Lilley, Warren (School of Education, 2014)
This research is concerned with how students and teachers in an Advanced South African EFL classroom construct meaning through the use of mobile phones. Drawing on CulturalHistorical Activity Theory (CHAT), I view mobile phones as cultural artefacts that learners and teachers use to engage in the construction of meaning-making practices. This use results in contradictions which potentially lead to radical transformation in the object and the subject positions offered in the classroom. Critical Discourse Analysis (CDA) is mobilised as a tool to explore power relations within a CHAT framework. This thesis is anchored in the critical tradition of research that problematises current global EFL materials and pedagogy which demonstrate very little critical engagement with or understanding of the myriad ways learners construct meaning in classes. A discussion of the research site is presented and the activity systems observed during the study are analysed. The dissertation then moves on to describe cases of student mobile phone use where the primary contradictions to the rules and object of the classroom activity system caused the teachers observed to enforce a tighter constriction of the division of labour between student and teacher. I relate these findings to deeper relations of power and authority in the EFL classroom, specifically to the constraints of teachers' institutional roles and how teachers construct and position EFL learners within South African EFL classrooms. This research provides key insight into the ways language learners' are (re)positioned and negotiate their mobile use within EFL classrooms through teachers' institutional roles and uptake of EFL pedagogy. It argues that the constraints and affordances of mobile phone use necessitate a deeper understanding of how EFL learners are attempting to 'communicate' in class, and in turn of how teachers are equally constrained by their position and pedagogy in recognising these endeavours. This study thus argues for a pedagogy that foregrounds 'possibility' in meaning making with mobile phones.